Ultrasound renal denervation: the future of hypertension management? - Laiba Ali; Hareer Fatima; Faiza Riaz; Muhammad Saqlain Mustafa; Burhanuddin Sohail Rangwala; Hussain Sohail Rangwala (The Egyptian Heart Journal, 2023)
Abstract Background Hypertension, a leading cause of global mortality and morbidity, affects approximately 1.28 billion adults worldwide, with most cases occurring in low- and middle-income countries. Despite several methods for managing mild to moderate hypertension, effective management of severe or resistant hypertension remains challenging. Renal denervation, a promising non-pharmacological technique, has emerged as a potential solution. Main body Renal denervation works by modifying the renal sympathetic nerve supply through techniques such as ultrasound, radiofrequency energy, or injection of neurolytic agents, reducing blood pressure. Clinical trials, including the RADIANCE series, have shown consistent effectiveness of ultrasound renal denervation in lowering blood pressure, especially in patients who were previously unresponsive to anti-hypertensive medications. After a follow-up of 2 months, mean ambulatory systolic blood pressure during the daytime decreased significantly in the ultrasound renal denervation group compared to the sham group. However, further research is needed to determine renal denervation's long-term safety and efficacy. Conclusions In conclusion, renal denervation holds great potential in improving the treatment of uncontrolled or resistant hypertension treatment, but more investigations and trials are necessary to establish its effectiveness and safety.